Effects of Wound Irrigation Using Pressure Controlled Technique on Satisfaction and Infection Among Persons with Lacerated Wound - บุสษา, วิภาณี; วังศรีคูณ, สุภารัตน์; สุคนธสรรพ์, อัจฉรา (Nursing Journal CMU, 2017)
Wound cleansing is an essential procedure to reduce risk of infection in lacerated wounds. This quasi-experimental research aimed to examine the effects of wound irrigation using the pressure controlled technique on satisfaction towards wound cleansing of persons with lacerated wounds and lacerated wound infection. The samples were 44 persons with lacerated wounds attending an emergency room. There were 22 persons in the control group which received routine wound cleansing. The 22 persons in the experimental group received wound irrigation using the pressure controlled technique. Subjects in both groups were matched according to wound size, wound location, time interval from injury to wound management, history of diabetes, and smoking. Wound irrigation using pressure controlled technique instrument was developed by the researcher and validated for wound irrigation pressure by an engineering expert. The instruments used for data collection included the Satisfaction Towards Wound Cleansing Evaluation Form and the Lacerated Wound Infection Evaluation Form, which were developed based upon the Center for Disease Control and Prevention wound infection criteria (Center for Disease Control and Prevention, 2013). Data were analyzed using descriptive statistics, the Mann-Whitney U test and the Fisher Exact Probability test. The study results revealed the following: 1. Satisfaction towards wound cleansing among persons with lacerated wounds in the experimental group (mean = 8.73, SD = 0.70, median 9.00) was statistically significantly higher than the control group (mean = 7.14, SD = 0.71, median 7.00) (p < 0.001). 2. The lacerated wound infection among the Subjects in both groups (control group 13.64%, experimental group 0%) was not statistically different (p = 0.12). The results of this study indicate that wound irrigation using the pressure controlled technique could be used for wound cleaning in a person with a lacerated wound.